2013
DOI: 10.1371/journal.ppat.1003581
|View full text |Cite
|
Sign up to set email alerts
|

The Secreted Antifungal Protein Thionin 2.4 in Arabidopsis thaliana Suppresses the Toxicity of a Fungal Fruit Body Lectin from Fusarium graminearum

Abstract: Plants possess active defense systems and can protect themselves from pathogenic invasion by secretion of a variety of small antimicrobial or antifungal proteins such as thionins. The antibacterial and antifungal properties of thionins are derived from their ability to induce open pore formation on cell membranes of phytopathogens, resulting in release of potassium and calcium ions from the cell. Wheat thionin also accumulates in the cell walls of Fusarium-inoculated plants, suggesting that it may have a role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 61 publications
(97 reference statements)
2
52
0
1
Order By: Relevance
“…(12) it was obvious that Thio63 protein cause more inhibition for the radial growth of both A. alternate and R. solani. These results agreed with [16] who worked on the secreted antifungal thionin protein isolated from Arabidopsis thaliana and suppressed the toxicity of fungal wall. …”
Section: Inhibitory Effect Of Protein Extracts On Radial Growth Of Fungisupporting
confidence: 90%
See 2 more Smart Citations
“…(12) it was obvious that Thio63 protein cause more inhibition for the radial growth of both A. alternate and R. solani. These results agreed with [16] who worked on the secreted antifungal thionin protein isolated from Arabidopsis thaliana and suppressed the toxicity of fungal wall. …”
Section: Inhibitory Effect Of Protein Extracts On Radial Growth Of Fungisupporting
confidence: 90%
“…As to their mode of action, thionins are known to form cation-selective ion channels by binding to phosphatidylserine head groups in lipid bilayer membranes which cause permeabilization and oxidative burst followed by cell death in target cells [49, 50 and 51]. The mechanism also explained simply by [16] as follow: the antibacterial and antifungal properties of thionins are derived from their ability to induce pore formation on cell membranes of phytopathogens, resulting in release of potassium and calcium ions from the cell. …”
Section: Pathogenicity Test:-mentioning
confidence: 99%
See 1 more Smart Citation
“…While [33] mentioned that the leaf explants were easily injured during the manipulation, which resulted in a low percentage of transformation.Thionin genesisolated from Arabidopsis thaliana were expressed in the transgenic potato cultivars and produced thionin proteins which have the ability to inhibit the fungal growth of both pathogenic fungi (Fusariumsolani and F. oxysporum). These results agreed with [16] who worked on the secreted antifungal thionin protein isolated from Arabidopsis thaliana and suppressed the toxicity of Fusariumgraminearum,also agreed with [34] who concluded that thionins inhibit the growth in vitro of about 20 different fungal plant pathogens including Botrytiscinerea, Fusarium spp., Phytophthorainfestans and Rhizoctoniasolani, [35] also observed that constitutive overexpression of an endogenous thionin in transgenic Arabidopsis resulted in enhanced resistance against Fusarium oxysporum f. sp. matthiolae, which indicates that thionins are defense proteins and [36] were also agreed with our work, who approved that the effective concentration of Thionins of type I, from the endosperms of wheat (Wal, Wa2, Wβ) and barley (Bα, Bβ), and of type II, from barley leaves (BLa, BLb, BLc),giving about 50% inhibition for strains of some bacterial species, such as Clavibactermichiganensis subsp.…”
Section: Discussionsupporting
confidence: 90%
“…N-and C-terminal amino acid sequences of these thionins are highly conservative but their nucleotide sequences differentiate to each other [13, 14 and 15]. The mechanism of thionins inhibition to the pathogenic fungi was simply explained by [16] as follow: the antimicrobial properties of thionins are derived from their ability to induce pore formation on cell membranes of phytopathogens, resulting in release of potassium and calcium ions from the cell. [17]mentioned that Agrobacterium-mediated transformation has become feasible.…”
Section: Introductionmentioning
confidence: 99%